(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Bangladesh is a small country of south Asia with a population of 153 million, among them 66 million are under age of 18years. The exact prevalence of chronic kidney disease (CKD) in children is not well known due to lack of a national registry. But in Bangabandhu sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, the incidence is 7.9% in 2013 and there are approximately thirty five hundred thousand around the country. There are 4.4% of children with renal disease prevalent in the country. But unfortunately, there is diagnostic problem and the treatment facility is very limited. Only few centers provide the renal replacement therapy in this country and only two centers do pediatric renal transplantation. So, to tackle this large burden with very limited resource, it is important to try and reduce the incidence of chronic kidney disease, especially end stage renal disease. We can handle the present situation with our existing resource with some modification of health care delivery system with contribution from government, non government organizations (NGO’S) and affluent people. This article highlights chronic kidney disease in children, present treatment modality and some fiiture directive to handle such a crucial problem, thus may help thousands of children from such a devastating situation. J Shaheed Suhrawardy Med Coll, 2015; 7(1):26-32